The Implication of the Indonesian Local Regulations Revocation towards the Local Economy and Out of Pocket Healthcare. (Medico Legal Update, 2020)
This research discusses the implication of the local regulation revocation towards the economic and health condition in a number of regions in Indonesia. And also, some of the cases which resulted in the implication conditions. This article was the result of a doctrinal study with literature review study and secondary data. The result of the research shows that (i) there is a government’s authority in revoking Perdas; (ii) the revocation of the local regulations in certain regions exerts adverse effect on the economy and healthcare. This article suggests that there is a need for the development of Perda with high-quality substances so that it can cope with the implication of legal regulations.